An experimental study and a proposed theoretical solution for the prediction of the ductile/brittle failure modes of reinforced concrete beams strengthened with external steel plates (Fracture and Structural Integrity, 2022)
An experimental study and a proposed theoretical solution are conducted in the present study to investigate the ductile/brittle failure mode of reinforced concrete beams strengthened with an external steel plate. The present experimental study has fabricated and tested six steel plate-strengthened RC beams and one non-strengthened RC beam under 4-point bending loads. The proposed theoretical model is then developed based on the observed experimental results to analyze the crack formation, to determine the distance between vertical cracks and to quantitatively predict the ductile/brittle failure mode of plate-strengthened RC beams. The experimental study shows that the failure mode is based on the sliding of concrete along with the external plate. This slip is limited between two vertical cracks, from which the maximum stress in the external steel is determined. Based on comparisons conducted in the present study, excellent agreements of the stresses/strains in soffit steel plates, crack distances, and system failure modes between the current theoretical solution and the previous and present experimental results are observed.
Keywords: strengthening reinforcement concrete beam; External steel plate; flexural reinforcement limit; tension chord model; ductile failure conditions